Hybrid Cannabis sativa L. inflorescences exert an anti-inflammatory effect through the modulation of MAPK/NF-κB/NLRP3 inflammasome and JAK1/STAT6 pathway in HaCaT cells - Han, Ji-Ye; Lim, Do-Won; Kwon, Osoung; Lee, Yun Jung; Choi, Hye Yung; Jung, Hyun-Ju; Noh, Soohyang; Cho, Mansoo; Kang, Sung Suk; Lee, Young-Mi (Frontiers in Pharmacology, 2025)
BackgroundAtopic dermatitis (AD) is a chronic inflammatory skin disease accompanied by severe itching. Reducing mediators of skin inflammation and itching is crucial for the treatment of AD. Cannabis sativa L. contains many types of cannabinoids and flavonoids, which exhibit antioxidant and anti-inflammatory effects. This study aims to demonstrate the anti-inflammatory and anti-atopic dermatitis effects of hybrid C. sativa L. inflorescence extracts (HCIE) in human keratinocytes.MethodsCannabis sativa extracts were analyzed using UPLC. Gene expression levels in HCIE-treated HaCaT cells were measured by RT-PCR, and intracellular ROS were evaluated using DCF-DA. Protein expression levels related to MAPK, NF-κB, NLRP3 inflammasome, and JAK1/STAT6 pathways were determined by immunoblotting.ResultsThe UPLC analysis revealed that a total of 8 cannabinoids were detected in HCIE. Among the cannabinoids identified in HCIE, CBDA and CBD were the most abundant, collectively accounting for approximately 28% of the total extract. The gene expression of MDC, RANTES, and TARC exhibited dose-dependent suppression in the HCIE-treated group. MAPK phosphorylation was inhibited in the HCIE-treated group. Additionally, NF-kB, p-NF-kB, NLRP3, and caspase-1 were reduced in a dose-dependent manner by HCIE. The activation of JAK1 and STAT6 was diminished in HaCaT cells treated with HCIE. Conversely, the levels of filaggrin and involucrin were significantly elevated in the HCIE-treated group compared to the control group.ConclusionTaken together, HCIE suppresses inflammation mediators through the regulation of the MAPK/NF-κB/NLRP3 inflammasome and JAK1/STAT6 pathways, while up-regulating skin moisturizing factors in keratinocytes. These results suggest that HCIE may be utilized in the treatment of skin inflammatory diseases, such as AD.